Processamento em diferentes soluções para obtenção de feijão seco com reduzido tempo de cozimento - Paz, Carlos Henrique de Oliveira (2020)
The Bean (Phaseolus vulgaris L) is one of the main sources of protein for many populations, with low cost, in comparison to animal protein. However, its consumption has been higher, having been reduced due to its long preparation time. The necessity for speed, convenience, and quality in the food preparation is the current reality and the processing industry seeks to meet these aspirations of the modern consumer. In order to reduce the cooking time of beans and other legumes, processing by maceration, a process in which the product remains soaked, before cooking, is a step that allows the absorption of water, essential to ensure softness and to reduce cooking time. Thus, the objective of the present study was to evaluate the effects of grains processing with maceration in different solutions in the quality parameters of Pinto beans, seeking to obtain a dry product with reduced cooking time and maintaining its characteristics in technological quality, using experimental planning techniques. In the first step of the study, Plackett & Burman planning was employed, evaluating the effects of seven factors in the processing: maceration time, sodium bicarbonate concentration (NaHCO3), potassium bicarbonate concentration (KHCO3), sodium carbonate concentration (Na2CO3), potassium carbonate concentration (K2CO3), potassium chloride concentration (KCl), and citric acid concentration (C6H8O7); under the responses: cooking time, percentage of damaged grains, hydration, total solids in the cooking broth, and difference in color of the processed grains compared to the control. In the second step, two plans of the DCC type were used, only with the factors that contributed to reduction of the cooking time and maintenance of technological quality. Grain processing, with concentrations of sodium carbonate and potassium carbonate above 1.5%, used in the maceration of beans, considerably reduced the percentage of damaged grains, the texture, and the cooking time of the grains; however, it darkened the bean tegument, increasing the color differences of the processed grains when compared to the control. The results obtained may contribute to further research on the development of technologies for processing beans with reduced cooking time.